Evolución reciente y claves actuales del Derecho Urbanístico Español - Iglesias González, Felipe (Pontificia Universidad Católica del Perú, 2022)
The purpose of this paper is to analyse the evolution of Spanish urban law in democracy. Spanish urban regulation has gone from a homogeneous state regulation to an increasingly heterogeneous regional regulation. For these purposes, the ruling of the Constitutional Court 61/1997, of March 20, was key, which encouraged the autonomous communities to approve their own urban codes, initiating a process of regulatory diaspora that continues. The most representative content of current state legislation is also studied, from the basic situations of land to the regime of transformation actions, through the valuation regime.

El objeto del presente trabajo es analizar la evolución del derecho urbanístico español en democracia. La regulación urbanística española ha pasado de una homogénea regulación estatal a una regulación autonómica cada vez más heterogénea. A estos efectos, fue clave la sentencia del Tribunal Constitucional 61/1997, de 20 de marzo, que incentivó que las comunidades autónomas aprobaran códigos urbanísticos propios, iniciándose un proceso de diáspora normativa que todavía perdura. También se estudia el contenido más representativo de la legislación estatal vigente, desde las situaciones básicas de suelo, hasta el régimen de actuaciones de transformación, pasando por el régimen de valoraciones.
Recent development and current keys on spanish urbanistic law
Keywords: Town planning; Town planning transformation actions; Legal duties; Town planning agreements; Appraisals; Legislation; Land classes; Urbanismo; Actuaciones de transformación urbanística; Deberes legales; Convenios urbanísticos; Valoraciones; Legislación; Clases de suelo; https://purl.org/pe-repo/ocde/ford#5.05.00